Design and Application of a Polarity Changing Sinusoidal Inverter Switching at Fundamental Frequency for Distributed Energy Systems - Akdemir, Huseyin; Eren, Yavuz; Boynuegri, A. R. (IEEE, 2018)
Renewable energy management and conditioning system for distributed generation (DG) has been a promising research topic due to the advantages on efficiency, energy quality and environmental effects. Recently, it has been emerged as an efficient tool to meet the demand by residential loads. There have been presented numerous studies about the integration of DG units with hybrid configurations of energy storage systems and renewable sources to supply the domestic loads via single phase inverters. In this paper, a novel operation strategy of a single phase inverter for DG systems has been proposed. The essential point of the proposed strategy has been based on to generate a rectified sinusoidal waveform on DC bus contrary to the conventional methods. The proposed operation strategy has been tested on Matlab (R)/Simulink environment and then it has been verified by an experimental study.
Keywords: Distributed Generation; Inverters; Single Phase Inverter; DC Bus; Rectified Sinusoidal Waveform; Computer Science; Energy & Fuels